Early centripetal displacements of capillaries in macular region caused by internal limiting membrane peeling - Kumagai K (Dove Medical Press, 2018)
Kazuyuki Kumagai,1 Nobuchika Ogino,2 Mariko Furukawa,1 Rieko Ooya,1 Eiji Horie3 1Kamiiida Daiichi General Hospital, Nagoya, Japan; 2Nishigaki Eye Clinic, Nagoya, Japan; 3Yata Eye Clinic, Izunokuni, Japan Purpose: The aim of this study was to determine whether the centripetal displacement of the capillaries in the macular region after vitrectomy is caused by internal limiting membrane (ILM) peeling. Methods: Eighteen patients with different types of retinal diseases but with a normal or approximately normal foveal contour underwent successful vitrectomy with (n=12) or without (n=6) ILM peeling. Optical coherence tomography angiography (OCTA) images of the inner retinal vascular plexus in the macular region were analyzed pre- and postoperatively. Four concentric polygonal areas were marked in the OCTA images with the corners selected to be easily identified by vessel bifurcations. The areas of the postoperative foveal avascular zone (FAZ) and the four polygonal regions at about 1 month postoperatively were compared to the baseline areas. Results: Vitrectomy was performed for eleven eyes with vitreomacular tractions, three with macular-on retinal detachments, and four with thin epiretinal membranes. A significant decrease in the FAZ area was observed postoperatively in only the ILM-peeled eyes (P=0.0002). The four polygonal areas in the ILM-peeled eyes decreased after surgery, and the decrease was fit by a linear regression line (R2=0.985–0.999; n=7). The time course of the postoperative decrease of the FAZ area was fit by a hyperbolic curve (R2=0.969–0.998; n=6). The average postoperative time required to reach one-half of the final FAZ area was 1.16 days (0.81–1.62 days). Conclusion: These findings suggest that ILM peeling causes an early centripetal displacement of the capillaries in the macular region. Keywords: epiretinal membrane, foveal avascular zone, internal limiting membrane, macular hole, optical coherence tomography angiography